2021
DOI: 10.3390/su13169075
|View full text |Cite
|
Sign up to set email alerts
|

“If I Was the Boss of My Local Government”: Perspectives of People with Intellectual Disabilities on Improving Inclusion

Abstract: Despite many initiatives to reframe and support inclusion for people with disabilities, people with intellectual disabilities continue to experience social exclusion in their local communities. This study shares the perspectives of people with an intellectual disability on what matters to them in their local communities. This study aims to inform local governments of the value of engaging with and listening to local people with intellectual disabilities and is an important exploration of how the social sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The research reported in this paper informs the results of a wider project designed to build the capacity of local governments in Australia to include people with intellectual disability in all aspects of citizen life with their Local Government Area (Carnemolla, Kelly, et al, 2021). Being embedded within local communities, local governments are well placed to lead the wider community towards social inclusion (Möller, 2020).…”
Section: Local Inclusion Buildingmentioning
confidence: 70%
See 1 more Smart Citation
“…The research reported in this paper informs the results of a wider project designed to build the capacity of local governments in Australia to include people with intellectual disability in all aspects of citizen life with their Local Government Area (Carnemolla, Kelly, et al, 2021). Being embedded within local communities, local governments are well placed to lead the wider community towards social inclusion (Möller, 2020).…”
Section: Local Inclusion Buildingmentioning
confidence: 70%
“…They did not want to be singled out as a particular group in need of specialist attention, but highlighted opportunities to think more broadly, collectively, about people who experience exclusion for a range of reasons. This emphasis connects to a growing body of scholarship on intersectionality (Carnemolla et al, 2021; Monro & Richardson, 2010; Richards et al, 2018), pointing to the multiple intersecting identities that all community members hold, and raising questions about how policy makers and local planners can, in turn, take a more holistic and nuanced approach.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have shown the importance of factors that improve healthy aging, ensure the social inclusion of the elderly, and prolong the time in which they can live independent lives [25]. Improving social sustainability in people with ID would mean improving social inclusion [26].…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out in Australia reported that the local government should listen to the voices of people with disabilities and value their input as an important exploration related to how the social sustainability of cities is framed [91]. Additionally, it is believed that tourist participation in tourism planning results in better support and attitudes, thereby leading to a more successful industry [92,93].…”
mentioning
confidence: 99%